2008
DOI: 10.1002/app.28376
|View full text |Cite
|
Sign up to set email alerts
|

Increasing recyclability of PC, ABS and PMMA: Morphology and fracture behavior of binary and ternary blends

Abstract: Binary and ternary blends of PC, ABS, and PMMA were studied. The blends were produced from original and recycled materials by melt mixing in a wide range of compositions. Instrumented Charpy impact testing, tensile testing, rheology investigations, and electron microscopy were carried out to determine the relationship between the deformation and fracture behavior, blend composition, morphology, and processing parameters. Resistance against unstable crack propagation was evaluated using the concepts of J-integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…The r-PC/r-ABS blends may also include PMMA as a third component (Laverty et al 1996;Rybnicek et al 2005). In this case, the chemical composition of the styrene-acrylonitrile matrix of ABS was found to have a dramatic effect on the morphology, while lubricant additives of ABS are adverse to the chemical stability.…”
Section: With Polymers Different From the Recycled Onementioning
confidence: 94%
See 1 more Smart Citation
“…The r-PC/r-ABS blends may also include PMMA as a third component (Laverty et al 1996;Rybnicek et al 2005). In this case, the chemical composition of the styrene-acrylonitrile matrix of ABS was found to have a dramatic effect on the morphology, while lubricant additives of ABS are adverse to the chemical stability.…”
Section: With Polymers Different From the Recycled Onementioning
confidence: 94%
“…However, all the compositions rich in PMMA exhibited inferior mechanical performance (Laverty et al 1996). A more detailed mechanical study (Rybnicek et al 2005) demonstrated that the transition from ductile elastoplastic behavior to brittle linear elastic fracture behavior occurs when the PMMA is above 10 wt%.…”
Section: With Polymers Different From the Recycled Onementioning
confidence: 97%
“…The surfaces of molded specimens were observed using a Hitachi S‐416, Japan (FE‐SEM) scanning electron microscope after sputter gold coating. The samples were cryogenically fractured and etched with a permanganic etching agent (solution containing 0.7 g of KMnO 4 , 20 mL of concentrated sulfuric acid, and 20 mL of phosphoric acid) to visualize PMMA and polybutadiene in ABS matrix 41. The surface of the specimens was immersed into the prepared solution for 15 min and then washed in running water.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of ABS degradation, Liu and coworkers showed that the polybutadiene (PB) phase was obviously reduced and that the styrene and acrylonitrile units remained relatively stable. This was due to the fact that the double bonds in the PB phase are prone to breakage; this results in a decrease in the molecular weight of the ABS and phase separation between the matrix and PB phase . These phenomena also exist during the degradation of PC/ABS blends.…”
Section: Introductionmentioning
confidence: 99%